MONITORING LOAD BALANCING SERVER E-LEARNING UNISBANK MENGGUNAKAN METODE LEAST - Dwi Budi Santoso; Jeffri Alfa Razaq; Fatkhul Amin Amin (STEKOM PRESS, 2023)
Implementation of Distance Learning (PJJ) is effective in the teaching and learning process during the pandemic. This is supported by Unisbank students in mastering information technology. PJJ technology, also known as e-learning, is a bridge between lecturers and students in the process of meeting in class into a meeting process in cyberspace. E-learning becomes ineffective when the demand for e-learning usage is high, causing server overload or crashes. When the e-learning server is overloaded, all parts that are usually connected and interrelated, such as lecturers, students, administration and others, become disconnected. The importance of monitoring the e-learning server to keep the e-learning load under control, and the server that has a lot of load will be divided so that e-learning will run smoothly and not be overloaded. Monitoring the Elearning server with the Least Connection method is applied to the Unisbank e-learning server and makes e-learning not overloaded. The results of the load balancer workload test with 1000 connections, the resulting response time is 0.2 ms, the workload is 5000 connections, the response time is 0.2 ms and the workload is 10,000 connections, the resulting reply time is 0.2 ms.